"All that glitters…": The Scientific and Financial Ambitions of Robert Bell at the Geological Survey of Canada - Brookes, Ian (Geoscience Canada, 2016)
SUMMARY In Canada, the 19th-century development of sciences with a geographical component was marked by individuals whose contributions were remarkable for their details, their geographical coverage, the originality and longevity of their ideas. Collectively, these individuals could be called the ‘inventors of Canada.’ Among them was Robert Bell. Early in his career at the Geological Survey of Canada and during an interval of part-time service while he taught at Queen’s University (1864–68), Kingston, Ontario, Robert Bell (1841–1917) involved himself in several commercial schemes that he hoped would lead to the development of mineral occurrences in the British colony of Newfoundland (various minerals), Canada East and West (petroleum), and Nova Scotia (gold), developments that he hoped would also raise his financial as well as his scientific stature. Here, the circumstances of these ventures and their outcomes and his unencumbered achievements in later life are reviewed.